A Melanocytic Lesion Extending From the Right Ear to the Nasopharynx in a Pediatric Patient: A Case Report. (August 2015) - Saito, Chizu; Ishikawa, Kotaro; Nakamura, Ken-ichi; Fujita, Akifumi; Shimizu, Michio; Fukushima, Noriyoshi; Nishino, Hiroshi; Ichimura, Keiichi
Background: Blue nevus is a benign dermal melanocyte tumor that mainly arises from the skin. We report an extremely rare case of blue nevus in a pediatric patient with extensive progression from the middle ear and inner ear to the nasopharynx through the Eustachian tube. Case Report: A 2-year-old girl with blue tympanum was referred to our department. Computed tomography scans and magnetic resonance imaging were performed, followed by a tissue biopsy and histopathologic evaluations. Radiologic examinations revealed that the lesion had progressed beyond the middle ear into the inner ear and the nasopharynx through the Eustachian tube. Subsequent histopathologic examinations indicated dermal dendritic melanocytic proliferations, but no evidence of malignancy. Based on the clinical and histopathologic findings, we concluded that the lesion was consistent with blue nevus. Discussion: Blue nevus is a relatively common skin lesion. However, no prior reports have described the extension of blue nevus from the auditory organ to the nasopharynx in a pediatric patient. Despite the benign nature of the lesion, the patient experienced profound hearing loss in the affected ear, which necessitates continued monitoring as the lesion may expand with patient growth.